Effectiveness of AstraZeneca vaccine against SARS-CoV-2 (ChAdox1-S) in reducing in-hospital mortality in individuals with COVID-19 and schizophrenia: A retrospective cohort study - Tiffany Dyu; Char Leung; Ana Cristina Simões- (Taylor & Francis Group, 2024)
ChAdOx1-S is a viral vector vaccine developed by AstraZeneca. We aimed to assess the effectiveness of 1 and 2 doses of the ChAdOx1-S vaccine in reducing COVID-19-related in-hospital mortality in individuals with schizophrenia. This is a retrospective cohort study using a nationwide hospital database in Brazil. Individuals diagnosed with COVID-19 and schizophrenia were included in the study. The exposures were 0, 1, and 2 doses of ChAdOx1-S. The outcome of mortality was measured in hazard ratios (HR), calculated using multivariable Cox regression models. The study included 1,929 positive cases of COVID-19 in schizophrenia patients. After adjusting for age, socioeconomic factors, and comorbidities, we observed a significant 55% decrease in the hazard of mortality in the 2-dose vaccination group (HR 0.45, 95% CI: 0.310-0.652) compared to the unvaccinated. Surprisingly, our results did not show any significant reduction in the hazard of mortality in the 1 dose vaccination group (HR 1.278, 95% CI: 0.910-1.795). The effectiveness of two doses of ChAdOx1-S in individuals with schizophrenia aligns with findings from studies on the general population. That one dose was insignificant. Overall, these findings are important for informing public health decisions - prioritizing individuals with schizophrenia for vaccinations and managing acceptance of vaccines.